Adoption Restraints in Mobile Banking with Reference to India - Deepa Damodaran; R. Regin; S. Suman Rajest (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
The number of people using mobile banking has been steadily growing over the past few years. Most of the time, this is the case in countries that are still developing or underdeveloped. It is proposed to investigate the comparative significance and distinctive influence of communication channels on customers' theories and attitudes regarding the adoption of mobile banking in India. This is despite the fact that the technology that provides services to the satisfaction of the user has not yet been investigated. "Perceived usefulness, perceived credibility, impact of communication channels, interpersonal networks, mass media, and social media" are the five primary variables that are incorporated into the study from a variety of perspectives. In the findings, it was discovered that the most important factors that influence the consumer's intention are the convenience of use and the cost. Banks ought to raise greater awareness and make it easier for customers to utilise themselves.